Cardiac Magnetic Resonance Predicting Outcomes Among Patients at Risk for Cardiac AL Amyloidosis - Agha, Ali M.; Palaskas, Nicolas; Patel, Amit R.; DeCara, Jeanne; Parwani, Purvi; Iliescu, Cezar; Durand, Jean B.; Kim, Peter; Hassan, Saamir; Gladish, Gregory; Lee, Hans C.; Kaufman, Gregory P.; et al. (Frontiers in Cardiovascular Medicine, 2021)
Introduction Patients with Systemic AL Amyloidosis (AL) should be evaluated for Cardiac Amyloidosis (CA), as prognosis is strongly related to cardiac involvement. We assessed characteristics of patients referred to Cardiac Magnetic Resonance (CMR) with suspected CA from a cancer center, and determine predictors of mortality/ heart failure hospitalizations (HFH). Methods 44 consecutive patients referred for CMR with suspected CA were retrospectively included. Variables collected included cardiac biomarkers, in addition to echocardiographic and CMR variables. Survival analyses were performed to determine which variables were more predictive of mortality and HFH. Results Of 44 patients included, 55% were females. 73% of patients were diagnosed with CA by CMR, 56% of them had an established diagnosis of AL. Patient with CA by CMR had higher native T1, higher Extracellular Volume fraction (ECV), higher T2, less negative GLS by Echo, higher troponin I and B-type Natriuretic Peptide (BNP). K-M Survival analysis revealed that the following were predictive of mortality: an ECV≥0.50 (p=0.0098), LVEF≤50% (p=0.0010), T2/ECV≤100 (p=0.0001) and troponin I > 0.03 (p=0.0025). In a stepwise conditional Cox logistic regression model, the only variable predictive of a composite of mortality and HFH was ECV (HR:1.17, 95%CI=1.02-1.34 p=0.030). Conclusion ECV seems to be an important biomarker that could be a predictor of outcomes in cardiac AL amyloidosis. In combination, CMR and serum cardiac biomarkers might help to establish prognosis in patients with CA.